2003
DOI: 10.1302/0301-620x.85b1.12925
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between cup design and the radiological signs of aseptic loosening in total hip arthroplasty

Abstract: We assessed differences in the incidence and appearance of the radiological signs of loosening of the cup for various types of design. This was an observational study based on hip registry data of 15,340 patients with 17,951 total hip arthroplasties collected over a period of 33 years in 49 hospitals in Central Europe. The threaded and the press-fit titanium cups showed significantly less aseptic loosening than the other systems. The direction of migration and the frequency of the radiological signs of looseni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 31 publications
(22 reference statements)
1
10
0
Order By: Relevance
“…More recently, intermediate results of noncemented acetabular components have shown significant decreases in failure rates attributed to aseptic loosening. However, radiographic evidence of radiolucencies adjacent to the acetabular component still exist and may be indicative of subsequent aseptic loosening and component failure [17,20]. Common noncemented acetabular components have the design characteristics that include low volumetric porosity, low coefficient of friction, and surface preparations that involve bonding to a solid substrate.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, intermediate results of noncemented acetabular components have shown significant decreases in failure rates attributed to aseptic loosening. However, radiographic evidence of radiolucencies adjacent to the acetabular component still exist and may be indicative of subsequent aseptic loosening and component failure [17,20]. Common noncemented acetabular components have the design characteristics that include low volumetric porosity, low coefficient of friction, and surface preparations that involve bonding to a solid substrate.…”
Section: Discussionmentioning
confidence: 99%
“…In two previous reports, the 10-year survival of acetabular components other than the CLS expansion cup used in metal-on-metal bearings ranged from 94 to 96% with revision for any reason and 95 to 99% with revision for aseptic loosening as the end point [26,27]. The 10-year survival of the CLS expansion cup disregarding the bearing couple with revision for any reason ranged from 92.7 to 100% in three different studies [34][35][36]. This raises the question whether the CLS expansion cup performs inferiorly in Metasul-based metal-on-metal THR.…”
Section: Discussionmentioning
confidence: 97%
“…On the acetabular side, comparative analyses of the large database of the Research Center in Orthopaedic Surgery of the University of Bern reported 10-year survivorship of uncemented press-fit (96.9%) and threaded (96.7%) titanium acetabular component designs [42]. Interestingly, the hazard ratio in the incidence of radiographic signs of loosening, adjusted for age and gender, was nearly twofold better for threaded titanium cups (0.16) than for press-fit titanium acetabular components (0.29), with cemented conventional PE acetabular components being defined as the reference level (1.00).…”
Section: Discussionmentioning
confidence: 99%
“…However, the intuitive advantages with the early design of cementless acetabular components may have been offset by an increased rate of conventional modular PE liner revisions resulting from deficient locking mechanisms, thin PE, and subsequent PE wear [21,42]. These facts are confirmed by US investigations on patients younger than 50 years of age using the Harris-Galante I press-fit cup (HG I; Zimmer, Warsaw, IN).…”
Section: Discussionmentioning
confidence: 99%